IMPLEMENTATION OF INVENTORY OF REGULATIONS, CONTROL OF LAND OWNERSHIP AND USE (IP4T) AT SIMPANG GAJAH MENTAH VILLAGE, SUNGAI RAYA DISTRICT, EAST ACEH MUNICIPALITY - Enny Mirfa; Fatimah Fatimah (Global Science Society, 2022)
Joint arrangement of the Minister of State in the Republic of Indonesia, the Minister of Forestry of the Republic of Indonesia, General Workers of the Republic of Indonesia, and Head of the Republic of Indonesia's Land Agency No. 79 of 2014, PB3/MENHUT-II/2014, 17PRT/M/2014, 8/SKB/X/2014 concerning procedures for settling land authorities in forest areas, is the basis for implementing the inventory of ownership, ownership, use and land use (IP4T) by the IP4T team in the context of completing land tenure within the forest area. The IP4T activity is a National Priority activity in the framework of supporting agrarian reform so that this activity must have a successful implementation which is one of the activities in the framework of achieving the fifth goal of the Jokowi-Jk Government's Vision and Mission, namely carrying out 9 million hectares of agrarian reform for the peasants / farm workers . In Gampong Simpang Gajah raw Sungai raya sub-district there are people who have mastered the land, but there is no land certification as proof of land ownership, therefore the East Aceh Land Agency through the IP4T program so that the community can issue their land certificates.